2014
DOI: 10.1007/jhep11(2014)098
|View full text |Cite
|
Sign up to set email alerts
|

Non-perturbative QCD effects in q T spectra of Drell-Yan and Z-boson production

Abstract: Abstract:The factorization theorems for transverse momentum distributions of dilepton/boson production, recently formulated by Collins and Echevarria-Idilbi-Scimemi in terms of well-defined transverse momentum dependent distributions (TMDs), allows for a systematic and quantitative analysis of non-perturbative QCD effects of the cross sections involving these quantities. In this paper we perform a global fit using all current available data for Drell-Yan and Z-boson production at hadron colliders within this f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 64 publications
(190 reference statements)
2
82
0
Order By: Relevance
“…But ref. [29] finds g K consistent with 0, which agrees with the present findings. However, one should take into account that contrary to standard fits, the present considerations are purely theoretical.…”
Section: Jhep03(2017)002supporting
confidence: 93%
See 1 more Smart Citation
“…But ref. [29] finds g K consistent with 0, which agrees with the present findings. However, one should take into account that contrary to standard fits, the present considerations are purely theoretical.…”
Section: Jhep03(2017)002supporting
confidence: 93%
“…The same model is also the core of the RESBOS program package [28] which is widely used in applications. On another hand, the implementation of TMDPDFs by [29] does not use b * -prescription. They have found that part of the non-perturbative corrections (essentially to the TMD evolution kernel) are negligible.…”
Section: Jhep03(2017)002mentioning
confidence: 99%
“…realizations used in refs. [1,11,25,39,41,42]. In this way the traditional implementation of the TMD cross-section contains four renormalization scale entries of the perturbative series and consequently four scales µ.…”
Section: Jhep08(2018)003mentioning
confidence: 99%
“…Resummations have been previously been discussed within an SCET [9][10][11][12] framework [29,30,[32][33][34][35][37][38][39] as well as in the CSS resummation formalism [40][41][42][43][44][45]. While formally most of the these…”
Section: Introductionmentioning
confidence: 99%